Mobility and stability adaptations in the shoulder of the overhead athlete: A theoretical and evidence-based perspective - Borsa, P. A.; Laudner, K. G.; Sauers, E. L. (Sports Medicine, 2008)
Overhead athletes require a delicate balance of shoulder mobility and stability in order to meet the functional demands of their respective sport. Altered shoulder mobility has been reported in overhead athletes and is thought to develop secondary to adaptive structural changes to the joint resulting from the extreme physiological demands of overhead activity. Researchers have speculated as to whether these structural adaptations compromise shoulder stability, thus exposing the overhead athlete to shoulder injury. Debate continues as to whether these altered mobility patterns arise from soft-tissue or osseous adaptations within and around the shoulder. Researchers have used quantitative techniques in an attempt to better characterize these structural adaptations in the shoulders of overhead athletes. Throwing athletes have been shown to display altered rotational range of motion (ROM) patterns in the dominant shoulder that favour increased external rotation and limited internal rotation ROM. Throwers also show a loss of horizontal or cross-body adduction in the throwing shoulder when compared with the non-throwing shoulder. This posterior shoulder immobility in the throwing shoulder is thought by some researchers to be associated with reactive scarring or contracture of the periscapular soft-tissue structures (e.g. posterior capsule and/or cuff musculature); however, evidence of reactive scarring or contractures of the posterior-inferior capsule or cuff musculature from anatomic or noninvasive imaging studies is lacking. Conversely, translational ROM (laxity) has been consistently shown to be symmetric between dominant and non-dominant shoulders of overhead athletes.